A new species of Kohleria (Gesneriaceae) from Southwestern Colombia - Arango-Gómez, Katherin; Clavijo, Laura; Zuluaga, Alejandro (Phytotaxa, 2021)
A new species of Kohleria (Gesneriaceae) is described from the Colombian Andes, in the departments of Huila and Cauca. The new species, Kohleria huilensis, has long been documented from the Merenberg Natural Reserve (La Plata, Huila), but has been confused with K. inaequalis var. inaequalis and K. inaequalis var. ocellata. The new species is distinguished by the following characters: white sericeous and sparse villous indumenta on vegetative structures; calyx lobes elongate with revolute margins; corolla magenta to fuchsia, ventral lobe orbicular with apex truncate; filaments hirsute with glandular trichomes distally; and staminodes < 2.8 mm long.